African American and Latino Men's Recommendations for an Improved Campus Environment. Issue 3 (October 2015) - Cerezo, Alison; Lyda, James; Enriquez, Alma; Beristianos, Matthew; Connor, Michael
<x xml:space="preserve">Abstract</x> The purpose of this study was to share findings from semistructured qualitative interviews with 9 African American and 12 Latino men about their ideas on how university personnel could better support their needs. Stressing the need for African American men to learn self–reliance to counter microaggressions, African American participants offered recommendations to students rather than personnel. Latino participants discussed the need for personnel to provide critical information about college resources.